Iraq Crude Oil Exports – July, August, September, October, November, December/ 2021 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2023)
Table 1. Iraq Crude Oil Exports – July 2021 Table 2. Iraq Crude Oil Exports – August 2021 Table 3. Iraq Crude Oil Exports – September 2021 Table 4. Iraq Crude Oil Exports – October 2021 Table 5. Iraq Crude Oil Exports – November 2021 Table 6. Iraq Crude Oil Exports – December 2021